“South Africa belongs to all who live in it” - Sarah Helen Chiumbu; Dumisani Moyo (Communicare)
A growing body of literature on media and xenophobia in South Africa has shown that the depiction of immigrants by the mainstream print media is overwhelmingly negative, and this in turn enforces negative stereotypes that contribute to further xenophobic attacks. This paper adds a dimension that is missing from existing research to focus on media representation of immigrants within questions around citizenship and identity.. The arguments driving this paper are inspired by the proclamations in the South African Constitution preamble, which states that “South Africa belongs to all who live in it, united in our diversity”. This paper analyses how selected print media in the country construct immigrants in the context of identity and belonging. We start from the premise that as a social institution, the media play an important role in shaping policies on immigration that have a bearing on these matters. Using theories of media and national identity, the paper examines thematic frames used by the selected newspapers to construct the image of immigrants during three periods of xenophobic violence, in 2008, 2015, and 2017. Our main argument is that while the media have played a significant role in creating awareness about the scourge of xenophobia, they have, wittingly or unwittingly, used narrative frames that justify the exclusion of foreigners, thereby entrenching a perception of insiders and outsiders, citizens and non-citizens. In the process, they also reinforce fears of a national takeover by the foreign “other”. These arguments hold significance in the broader debates about the transformation of the print media and its role in the on-going process of nation-building.